Water balances in the Eastern Mediterranean - Brooks, David B., 1934-; Mehmet, Ozay (International Development Research Centre, 2000)
The roots of destabilization, migration, and local conflict around the world can often be traced to a lack of fresh water. As a result, the importance of fresh water to economic development, quality of life, ecosystem sustainability, and political stability is gaining renewed global recognition. In the Middle East and the countries of the Eastern Mediterranean region, the situation is approaching crisis proportions. People living in this part of the world have only one-sixth as much fresh water available per capita as the global average. Although predictions of a Middle Eastern ''water war'' a.